2014
DOI: 10.1371/journal.pone.0090826
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Strategies and Biodiversity of Influenza A Subtypes in Wild Birds

Abstract: Wild aquatic birds are recognized as the natural reservoir of avian influenza A viruses (AIV), but across high and low pathogenic AIV strains, scientists have yet to rigorously identify most competent hosts for the various subtypes. We examined 11,870 GenBank records to provide a baseline inventory and insight into patterns of global AIV subtype diversity and richness. Further, we conducted an extensive literature review and communicated directly with scientists to accumulate data from 50 non-overlapping studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 39 publications
1
45
0
1
Order By: Relevance
“…2) indicated that the H12 HA gene first reassorted with an unsampled NA subtype between 1997 and 2003, and the resultant virus reassorted with an H1N3 virus between 2006 and 2009, giving rise to the H12N3 subtype. Given the promiscuity of H12 and N3 with other NA and HA subtypes respectively [26], we believe this to be a plausible explanation for this virus' emergence. However, owing to the limited number of H12N3 sequences available in the public database, the definitive conclusions on reassortment are difficult to ascertain.…”
mentioning
confidence: 87%
“…2) indicated that the H12 HA gene first reassorted with an unsampled NA subtype between 1997 and 2003, and the resultant virus reassorted with an H1N3 virus between 2006 and 2009, giving rise to the H12N3 subtype. Given the promiscuity of H12 and N3 with other NA and HA subtypes respectively [26], we believe this to be a plausible explanation for this virus' emergence. However, owing to the limited number of H12N3 sequences available in the public database, the definitive conclusions on reassortment are difficult to ascertain.…”
mentioning
confidence: 87%
“…Rather, resource allocation could be prioritized to provide sustained surveillance in a few targeted locations and in specific seasons that maximize information on viral diversity relevant to potential spread (e.g., high-risk species, species interfaces, major staging and migration stopover sites, and reassortment hotspots [ 23 ]). Recent analysis of avian influenza virus subtype diversity and richness suggests that 75% of HA and NA subtype diversity in wild birds could be captured through targeted surveillance efforts in the Northern Hemisphere over a 4-year period ( 24 ). …”
Section: Targeted Country Participationmentioning
confidence: 99%
“…Although we propose an initial focus on the Northern Hemisphere to leverage current investments and target surveillance on the basis of prior avian influenza study findings reported above ( 24 , 25 ), we do not intend to undermine the role of efforts elsewhere. We especially acknowledge that bias in surveillance effort has limited current knowledge on avian influenza virus diversity in the Southern Hemisphere ( 4 ).…”
Section: Targeted Country Participationmentioning
confidence: 99%
“…A lot of them are sporadically transmitted to other birds, in particular to chickens, causing outbreaks of fowl pest. Where contacts of fowl and humans are close like in China and South-East Asia, direct transmission to humans happens usually causing severe respiratory disease, by which the public health services are alerted and instant measures are taken to prevent an epidemic [27,28]. Concerning these cases, a lot of new research on influenza pathogenicity was done [29][30][31][32].…”
Section: Successes and Failures Of Vaccine Developmentsmentioning
confidence: 99%